How effective are external cues and analogies in enhancing sprint and jump performance in academy soccer players? - Moran, J.; Allen, M.; Butson, J.; Granacher, U.; Hammami, R.; Clemente, F. M.; Klabunde, M.; Sandercock, G. (Journal of Sports Sciences, 2023)
This study investigated the effect of external (EC) and internal coaching cues (IC), analogies with a directional component (ADC) on sprint (20 m) and vertical jump performance in academy soccer players (n = 20). A repeated-measures analysis, with post-hoc comparisons, was used to identify any differences between these cues and a neutral (control) cue. Significant differences were found for both sprint (p < 0.001) and jump (p = 0.022) comparisons among cue types. In post-hoc analyses for the 20 m sprint, significant differences were observed between the EC and the IC, favouring the EC (p < 0.01, ES = 1.27 [CI: 0.24, 2.30]), and "away" ADC and the IC, favouring the "away" ADC (p < 0.01, ES = 1.21 [CI: 0.19, 2.22]). No other cues showed significant differences. For vertical jump, there was just one significant difference between comparisons, that being for the "away" ADC vs. the neutral cue, favouring the latter (p = 0.023, ES = 0.4 [CI: -0.04 to 0.84]). It appears that ECs and ADCs are most effective when coaching sprinting performance in academy soccer players. However, simply encouraging maximal effort from a youth athlete also appears to be a reasonable cueing strategy to drive performance in youth athletes.